Design de superfície: o bordado manual como interferência têxtil - Trannin, Mariane Rodrigues (2015)
The objective of this work is to use the embroidery techniques in surface design. To this end, will prove to the craft techniques and manuals have always been present in many aspects of the story, especially in clothing, and played an important role in the development and improvement of artistic sewing, and are still present in the modeling made in XXI century. In this work, study will be embroidery techniques through the use of various materials such as aljofre, bugle beads, glass beads, crystals, threads, beads, etc., by encapsulating them in the surface design. It starts with the premise that the embroidery, although it is an ancient technique, can contribute to the sophistication and the surface design refinement, adopted nowadays. The research literature is to study the theoretical elements, and practice in creating collection which will highlight the embroidery on the textile surface.